TRANSFORMATIONAL LEADERSHIP OF THE SCHOOL PRINCIPAL IN IMPROVING EDUCATOR QUALITY IN THE DIGITAL MODERNIZATION ERA AT SLB AT TANHID PAKEL, TULUNGAGUNG - Nur Hidayati (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
The current complex and global nature of digital development is driving significant digital transformation across various sectors of life, including education. This situation places the school principal at the forefront of managing change and enhancing educational quality in the digital era. This study aims to comprehensively analyze the transformational leadership of the school principal in improving educational quality in the digital era, using a case study at SLB At Tanhid Pakel, Tulungagung. Specifically, the study examines strategic transformational leadership measures and their impact on educational quality. A qualitative case study approach was employed. Data were collected through interviews, observations, and documentation, and subsequently analyzed using the Miles and Huberman interactive model—comprising data condensation, data display, and conclusion drawing—with triangulation used to ensure data validity. The results indicate that the principal implemented digital transformation through the formulation of a school digital vision, mapping of teacher competencies, strengthening of technological infrastructure, creation of an innovation culture, and development of an adaptive curriculum. Transformational leadership was shown to have a significant impact on enhancing teacher competence, optimizing digital learning, improving student achievement, fostering a collaborative work culture, and ensuring school readiness to face educational challenges in the digital era.